Ethical preparedness in genomic medicine: how NHS clinical scientists navigate ethical issues - Sahan, K; Lyle, K; Carley, H; Hallowell, N; Parker, MJ; Lucassen, AM (BMJ Publishing Group, 2024)
Much has been published about the ethical issues encountered by clinicians in genetics/genomics, but those experienced by clinical laboratory scientists are less well described. Clinical laboratory scientists now frequently face navigating ethical problems in their work, but how they should be best supported to do this is underexplored. This lack of attention is also reflected in the ethics tools available to clinical laboratory scientists such as guidance and deliberative ethics forums, developed primarily to manage issues arising within the clinic. We explore what ethical issues are being experienced by clinical scientists, how they think such issues could be best analysed and managed, and whether their practice might be enhanced by more situated approaches to ethics deliberation and practice such as ethical preparedness. From thematic analysis of cases presented by clinical scientists at a specially convened meeting of the UK Genethics Forum, we derived three main ethical themes: (1) the redistribution of labour and responsibilities resulting from the practice of genomic medicine; (2) the interpretation and certainty of results and (3) the proposal that better standardisation and consistency of ethical approaches (for example, more guidelines and policy) could resolve some of the challenges arising. We argue that although standardisation is important for promoting shared understandings of good (including ethical) practice, supplementary approaches to enhance and sustain ethical preparedness will be important to help clinical scientists and others in the recently expanded genetic/genomic medicine environment foster quality ethical thinking.